A Template for a Soul-Winner and Soul-Winning Sermon from Apostle Peter’s Life and Preaching in Acts 2:14-41 - Favour Ogundiran (African Theological Journal for Church and Society)
One of the primary purposes of preaching is soul-winning. This paper examines Apostle Peter’s life and preaching on the Day of Pentecost in Acts 2, where at least three thousand souls were won and added to the Church. Consequently, a template is developed from Peter for a soul-winner and soul-winning sermon. This template involves the preacher’s personal life and the preacher’s sermon. Beyond the initial crowd’s bewilderment at hearing the disciples speaking in their various languages was the response of three thousand men to Peter’s preaching. When the people heard his sermon, they were cut to the heart and said to Peter and the other apostles, ‘Brothers, what shall we do?’ To win souls, every preacher needs the empowerment of the Holy Spirit to elicit the audience’s response to the invitation to salvation. Response to the invitation is evidence of a soul-winning sermon.